Determination of Wavelength Shift of Fiber Bragg Grating Sensors by Tunable Single-mode Diode Laser - Anh, Nguyen The; Son, Pham Thanh; Van, Nguyen Thuy; Cam, Hoang Thi Hong; Minh, Ngo Quang; Huy, Bui; Hoi, Pham Van (Communications in Physics, 2013)
We propose a novel principle of determination of fiber Bragg grating (FBG) wavelength shift which is impacted by a variation of physical parameters such as temperature, pressure and/or strain. In common case the wavelength shift of FBG was monitored by wavelength measurement using a high-cost spectrometer and a broad band light source. In our proposed technique the wavelength shift of FBG can be determined by change of lasing wavelength of distributed feedback laser (DFB-laser) due to the change of laser substrate temperature. The maximal opto-electrical intensity of photodetector would be obtained when the laser wavelength and FBG reflection wavelength are coincided. The FBG sensor prototype has shown excellent response for laser temperature change in the range of \(10^°C-50^°C\) with the ratio \(Δ λ /Δ T\) of the DFB laser is of 77.5 pm.K\(^ - 1\). Key features of the proposed technique are fabrication of low-cost FBG sensors for civil engineering.